METHODS AND METHODS OF PSYCHOLOGICAL AND PEDAGOGICAL STUDY OF TEENAGE CHILDREN. PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF TEENAGE CHILDREN - Rimbayeva Ozoda Bazarbayevna (Western European Studies, 2024)
adolescence is important in children's lives. During this period, psychological and physiological changes occur in children. Children remain influential and changeable. This article provides information about the methods and methods of psychological and pedagogical education of children of adolescent age and their psychological and pedagogical characteristics.
Keywords: psychological trait; pedagogical trait; adolescent child